(untitled) (Czech Journal of International Relations, 2024)
This study examines how climate-vulnerable states charge major carbon emitters with bad faith behaviors, how those emitters respond in ways that often confirm the bad faith charges, and what vulnerable states propose as policy alternatives. Using an existentialist conceptualization of bad faith and Bassan-Nygate and Heimann’s four response mechanisms – projection, distortion, displacement, and rationalization – we identify how major emitters try to negate bad faith claims in ways that are deceptive of the self and the other. Major emitters require self-ref lection to identify how they are not meeting international climate policy agreements and begin to address what they must change (about themselves), but vulnerable states note that this ref lection is absent. This study of 399 speeches by national leaders at three climate summits opens directions for scholars, activists and policymakers to understand how interactions around bad faith illuminate the politics of bad faith and the potential for change this contains.